Limber tail syndrome in German shepherd dog (Veterinary Science Development, 2015)
A 3-year-old intact female German shepherd dog weighing 25 kg was evaluated for acute onset of staggering gait and flaccid (dropped) tail following immersion in freeze water. Clinical signs included staggering gait, aggressive behavior, postural pain and flaccid tail. Clinical signs progressed in severity for 2-3 hours following immersion in freeze water. The dog was treated using anti-inflammatory medication along with warm fomentation of the affected portion of the tail and complete rest. Dog uneventfully recovered on day 7 of initiation of treatment and no reoccurrence was observed during one month follow up period. Limber tail syndrome is an uncommonly reported condition in German shepherd dogs that should be considered when sudden staggering gait and dropped tail is observed after immersion in too cold water. Recovery is possible with anti-inflammatory drugs and rest.